Implications of successive blood feeding on Wolbachia-mediated dengue virus inhibition in Aedes aegypti mosquitoes - Rebecca M. Johnson; Mallery I. Breban; Braiya L. Nolan; Afeez Sodeinde; Isabel M. Ott; Perran A. Ross; Xinyue Gu; Nathan D. Grubaugh; T. Alex Perkins; Doug E. Brackney; Chantal B. F. Vogels (Nature Communications)
Abstract Wolbachia is a promising strategy to inhibit dengue virus (DENV) transmission by Ae. aegypti mosquitoes. Laboratory studies assessing DENV inhibition by Wolbachia typically have not considered natural frequent mosquito blood feeding behavior. Here, we determine the impact of successive feeding on DENV-2 transmission by Ae. aegypti in the presence or absence of Wolbachia (wAlbB and wMelM strains). We show that successive feeding shortens the extrinsic incubation period (EIP) in wildtype (WT; without Wolbachia) and wAlbB mosquitoes through enhanced dissemination. Feeding empirical data into models showed that successive feeding increases the probability of WT and wAlbB mosquitoes surviving beyond the EIP. Importantly, the more epidemiologically relevant comparison of the odds of wAlbB mosquitoes surviving beyond the EIP relative to WT, reveals a larger impact of successive feeding on WT than wAlbB. This indicates a strong inhibitory effect of Wolbachia even in the context of natural frequent mosquito blood feeding behavior.